Demand and Supply: A Case Study of Meat Price Fluctuations at Pasar Baru-Jayapura Ahead of Hari Raya - Pakiding, Seofri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
December marks the end of the month with a vivid array of bustling activities and market events that significantly stand out. This market activity is influenced by the Christmas and New Year's moments, leading to a surge in demand for chicken and pork in Jayapura, Papua. The purpose of this research is to analyze the fluctuation patterns of chicken and pork prices and their contributing factors. The applied method in this study is a qualitative descriptive method using data collection techniques through interviews and document analysis of the ledger books of chicken and pork traders in Pasar Baru, Jayapura, Papua. The interview technique involves in-depth interviews with a sample of 3 chicken traders and 2 pork traders, accompanied by recording techniques. The interview results are then recorded or transcribed by converting oral text into written form. The transcribed results are further processed using the reduction technique, eliminating irrelevant text and grouping selected text for presentation as presentation data to be analyzed using domain analysis. Meanwhile, document analysis is conducted to categorize three income or debit sections based on the time of sale classification, namely early December, approaching Christmas and New Year, and post-New Year. The research results indicate that factors influencing price fluctuations are production factors and the quality of chicken and pork products, local cultural intervention factors, marketing strategy and management factors, consumer purchasing power or consumer behavior, and market nature or demand factors. Document analysis shows a significant increase in demand leading up to Christmas and New Year's Day, adhering to the law of supply and demand in direct proportion.